The architecture of apophasis: exploring options for a cognitive scientific interpretation of the via negativa - Hollingsworth, Andrea (Religion, brain & behavior, 2016)
This article charts possibilities for discerning cognitive mechanisms that mediate apophatic cognition (and its purportedly self-transforming effects) in negative streams of Christian thought and practice. First, it tests the extent to which (1) Schjoedt’s et al. "cognitive depletion" model (Schjoedt et al., 2013) and (2) McNamara’s "decentering" model (McNamara, 2009) can explain, biologically and psychologically, why epistemic and existential loss is often said to precede and attend illumination in the via negativa - or negative way. While McNamara’s theory proves more convincing than Schjoedt’s et al. for shedding light on cognitive underpinnings of the negative way, neither theory is fully satisfactory because neither adequately accounts for the constitutive role of social and emotional dynamics at each step in the Christian apophatic journey. The final section introduces a cognitively informed account of the apophatic path consisting of four moments: Resonance, Rupture, Reappraisal, and Repair. This account is supported largely by a turn to neurocognitive, developmental, and clinical psychological research on relationality and emotion regulation.